Flavonoids from the Rhizomes of Kaempferia Parviflora Wall. Ex Baker - Loan, Ly Tu; Hue, Phan Thi Ai; Thanh, Ma Chi (VNU Journal of Science: Natural Sciences and Technology, 2023)
Kaempferia parviflora Wall. ex Baker, Zingiberaeceae has been used in traditional medicine in Vietnam for the treatment of inflammation, abdominal pain, indigestion, menstrual cramps, fatigue. From the n -hexane fraction of the rhizomes of Kaempferia parviflora , six compounds were isolated and determined as 5-hydroxy-3,7-dimethoxyflavone ( 1 ), 5,7-dimethoxy chrysin ( 2 ), 5-hydroxy-7-methoxyflavone ( 3 ), 5-hydroxy-3,4',7-trimethoxyflavone ( 4 ), 4',5,7-trimethoxyflavone ( 5 ), and 3,4',5,7-tetramethoxyflavone ( 6 ). The structures of 1-6 were elucidated by extensive spectroscopic methods (MS, 1D, and 2D NMR)